INFLUENCE OF DIURNAL CYCLES ON METAL CONCENTRATIONS AND LOADS IN STREAMS DRAINING ABANDONED MINE LANDS: AN EXAMPLE FROM HIGH ORE CREEK, MONTANA - Gammons Ch.H.; Milodragovich L.; Belanger-Woods J. (My University, 2007)
Diurnal water samples were collected simultaneously at four locations along High Ore Creek (Montana, USA), a small stream with near-neutral pH that contains elevated concentrations of Zn, Mn, Cd, and As from abandoned mines near its headwaters. During the same time period, two sets of synoptic samples were collected by workers moving in opposite directions along the stream. Large diurnal fluctuations in Zn concentration were found at three of the 24-h monitoring stations, but not at the outlet to a settling pond. Because the concentrations of Zn were dropping at most locations in the creek during the day (in response to the daily cycle of day-time attenuation and night-time release), the synoptic sampler who moved upstream obtained a data set that led to the conclusion that Zn load increased with distance downstream. The sampler who moved in a downstream direction obtained the opposite results. Thus, failure to take short-term diurnal cycling into account can lead to incorrect conclusions regarding spatial or temporal trends in water quality within a watershed.
Keywords: DIEL; DIURNAL; ZINC; ARSENIC; GEOCHEMISTRY